(untitled) (Historia, 2021)
English Government control and legislation regarding urban black housing before and during the Second World War In the years before and during the Second World War the tempo of black urbanisation increased tremendously. This rapid urbanisation caused the demand for urban black housing to sky-rocket. The urban local authorities were compelled by legislation to provide the urban blacks under their jurisdiction with accommodation since the 1920’s. Legislation enabled the urban local authorities to create, finance and maintain black housing. Legislation also provided for influx control. As a result of the economic demands of the Second World War and the increasing permanent nature of black urbanisation, the urban local authorities were not able (or willing) to enforce these legislative stipulations strictly. The consequences were uncontrolled black urbanisation and a housing need and crisis that laid the foundation for the present-day problems regarding black housing. Afrikaans In die jare voor en gedurende die Tweede Wêreldoorlog het die tempo van swart verstedeliking geweldig toegeneem. Hierdie snelle verstedeliking het die vraag na stedelike swart huisvesting die hoogte laat inskiet. Die stedelike plaaslike owerhede is vanaf die 1920’s deur wetgewing verplig om huisvesting aan die stedelike swartes binne hul gebiede te voorsien. Wetgewing het dit vir die stedelike plaaslike owerhede moontlik gemaak om swart behuising daar te stel, te finansier en in stand te hou. Wetgewing het voorts ook vir instromingsbeheer voorsiening gemaak. Weens die ekonomiese eise van die Tweede Wêreldoorlog en die toenemende permanente aard van swart verstedeliking was die stedelike plaaslike owerhede nie by magte (en gewillig), om genoemde wetbepalings nougeset toe te pas nie. Die gevolge hiervan was onbeheersde swart verstedeliking en ’n behuisingsnood en -krisis wat die grondslag gelê het vir die hedendaagse probleme rakende swart behuising.